Effect of Chronic Smoking on Plasma Antioxidant Enzyme Activity - Abdulkadhim Kareem Abbood Zerjawi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Oxidative stress is caused by regular smoking. If oxidative stress is higher than the level of antioxidants, there is said to be oxidative stress. SOD, CAT and GPx enzymes in the plasma help to reduce the harm caused by oxidative stress. This study aimed to discover if smoking regularly had any impact on the enzymes found in adults. A total of 120 people, with 60 chronic smokers and 60 nonsmokers, took part in the study and each group of 60 had equal numbers of men and women. All donors of blood and plasma had their levels of SOD, CAT and GPx checked using regular spectrophotometric procedures. I carried out the analysis using SPSS software version 26.0. The levels of SOD (1.82 ± 0.29 U/mL), CAT (31.5 ± 4.8 IU/mL) and GPx (3.21 ± 0.52 IU/mL) were lower in smokers compared to non-smokers. The gender levels showed the same effect on the study results as the smoking levels and did not interact with one another. Generally, regular smoking can decrease the amount of this enzyme working in plasma, so the body becomes less able to protect itself from oxidation for both men and women. It indicates that smoking leads to a health issue and advises taking actions to decrease risks for smokers.